The photocopied 1990s: youth, culture, and fanzines - Altun, Murat. (Thesis (M.A.)-Bogazici University. Atatürk Institute for Modern Turkish History, 2005., 2005)
This thesis strives to elucidate the cultural transformation of a period, the 1990s, considering fanzines as products of youthful experiences. The 1990s are conceptualized throughout the thesis following the argument of "Society of the Spectacle" which is very fruitful to grasp the evolution of youth from a social category to a symbolic capital full of exclusionary concepts. With a different perception of youth in a historically constructed perspective, thesis seeks to negate a common public mood in the post-1980s years that claimed the apoliticalness and the silence of the non-adult members of society. In that sense, despite their anti-social andpessimist satire, the thesis takes fanzines as "social-texts" produced by youthful experiences to survive in a climate of cultural transformation that displaced all recognized social identifications. Therefore, the thesis stands on three main bodies, namely youth, culture, and fanzines in order to demonstrate the reciprocal process of the determination of historical context and the social text and its subject. On the other hand, although fanzines pinpoint a very small extent of youthful experiences, they may help to remember a history which is not merely full of repression and fragmentation, but also of possibilities and refusals which reckoned with their present, not a glorified past or promising future. As a consequence, fanzines as a spectacular response to the reign of spectacle, within a historicist framework, may present the clues to many in order to guide their struggle to survive in an everydayness that is collapsed and rebuilt by the new culturalist turn of global capitalism.
Keywords: Youth -- Turkey -- Political activity.; Youth -- Turkey.